Throwing Stick to Spear Thrower - Study of Ethnographic Artefacts and Experimentation - Luc Bordes (EXARC Journal)
Little is known about the process of the invention of the prehistoric spear thrower which appeared around 25,000 years ago in Europe, although it may have emerged earlier on other continents. This innovative weapon had a late arrival in Australia from Papua New Guinea at the end of the late glacial maximum, and probably induced an adaptation in hand throwing spear technology used by local people. But could the spear thrower have also originated independently from older prehistoric technology on this continent? In this work, the hypothesis of a technological evolution from throwing sticks to the spear thrower is examined through several particular wooden Australian Aboriginal implements observed in ethnographic collections. Indeed, some traditional Aboriginal hooked throwing sticks from Coopers Creek might be a trace of a prehistoric throwing stick/spear thrower technological complex which has disappeared to be replaced by true specialised spear throwers from New Guinea, rendering them obsolete. Interestingly, other intersections between these two weapons could be found in the particular type of “on edge” built Aboriginal spear throwers from Northern Queensland where rare examples of spear throwers made from modified throwing sticks can also be found. Do they result from an adaptation of throwing sticks in contact with spear thrower importations from New Guinea or do they reflect the continuity of an older, independent Indigenous Australian spear thrower invention? Experimental replicas and throwing tests have been used here to try to shed light on the potential and limits of such implements which could have been used simultaneously for both functions.